Ulysses proficiens. A reassessment of Seneca’s reading - Carlo G. Delle Donne (Rónai – Revista de Estudos Clássicos e Tradutórios, 2021)
This article offers a new reading of Seneca’s Ulysses. He will be proven not to stand for the Stoic hero, the symbol of virtue; rather, he will turn out to represent the proficiens – those who make any effort to reach virtue, and yet sometimes fail. In this regard, Ulysses is like Seneca himself, in as much as both of them appear to do their best to face the impetuous waves of fortune.